The Effect of General Anaesthesia on Circadian Rhythms in Behaviour and Clock Gene Expression of Drosophila melanogaster - Nina Li; Ralf Stanewsky; Tessa Popay; Guy Warman; James Cheeseman (Clocks & Sleep, 2020)
General anaesthesia (GA) is implicated as a cause of postoperative sleep disruption and fatigue with part of the disturbance being attributed to a shift of the circadian clock. In this study, Drosophila melanogaster was used as a model to determine how Isoflurane affects the circadian clock at the behavioural and molecular levels. We measured the response of the clock at both of these levels caused by different durations and different concentrations of Isoflurane at circadian time 4 (CT4). Once characterized, we held the duration and concentration constants (at 2% in air for 6 h) and calculated the phase responses over the entire circadian cycle in both activity and period expression. Phase advances in behaviour were observed during the subjective day, whereas phase delays were associated with subjective night time GA interventions. The corresponding pattern of gene expression preceded the behavioural pattern by approximately four hours. We discuss the implications of this effect for clinical and research practice.